2014
DOI: 10.1097/wnr.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the neurotrophic factors BDNF, NT-3, and FGF2 on dissociated neurons of the cochlear nucleus

Abstract: The cochlear nucleus is the first relay station for acoustic information in the auditory pathway and its cellular integrity is affected by hearing loss. Neurotrophic factors, which are known to regulate fundamental processes in the brain, are expressed in the cochlear nucleus and are regulated by the changes in the stimulation. The aim of this study was to evaluate the effect of the neurotrophins Brain derived neurotrophic factor (BDNF) and Neurotrophin 3 (NT-3) and the neurotrophic factor Fibroblast growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…At present, it is believed that the occurrence of POCD is caused by neuronal necrosis and apoptosis via multiple pathways. Previous animal experiments have indicated that at the onset of POCD, the expression of BDNF is markedly enhanced, which may significantly alleviate ischemic brain injury, inhibit neuronal death, and exert neuroprotective effects (35,36). In the present study, the protein expression levels of BDNF were increased following treatment of isoflurane-treated rats with nobiletin.…”
Section: Discussionsupporting
confidence: 54%
“…At present, it is believed that the occurrence of POCD is caused by neuronal necrosis and apoptosis via multiple pathways. Previous animal experiments have indicated that at the onset of POCD, the expression of BDNF is markedly enhanced, which may significantly alleviate ischemic brain injury, inhibit neuronal death, and exert neuroprotective effects (35,36). In the present study, the protein expression levels of BDNF were increased following treatment of isoflurane-treated rats with nobiletin.…”
Section: Discussionsupporting
confidence: 54%
“…BDNF expression is absent from all auditory nuclei in the brainstem at birth (Hafidi, 1999), but BDNF and NT-3 positive neurons are widely distributed in the CN beginning in the early post-natal period at about P6 (Hafidi, 1999; Tierney et al, 2001; Wiechers et al, 1999). Further, in vitro studies of the CN, showed an upregulation of BDNF expression in the AVCN and PVCN 3 days after unilateral cochlear ablation in the guinea pig (Suneja et al, 2005), and a study of dissociated neurons of neonatal rat CN (Rak et al, 2014) demonstrated that BDNF stimulated neuronal survival and axonal outgrowth. The results of our current study showing that the total CN volume and spherical cell size were significantly larger on the BDNF-treated side than on the contralateral side, are consistent with these previously reported findings of neurotrophic effects of BDNF in the CN.…”
Section: Discussionmentioning
confidence: 99%
“…They can affect the development of the nervous system in multiple ways, regulate the distribution of neurons, and promote the repair and regeneration of neurons and synapses. Studies have shown that a variety of factors, including BDNF, NT3, CNTF, GDNF, NT4/5, neurturin, artemin, TGF, and FGF[8, [27][28][29], are involved in the development of inner ear tissue and survival of hair cells and SGNs.…”
Section: Expression Of Ntfs In the Auditory Systemmentioning
confidence: 99%